IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) PADA MATA PELAJARAN FIQIH KELAS VIII MTSS FASTABIQUL KHAIRAT GUNUANG MALINTANG PANGKALAN KOTO BARU - Novia Eka Sari; Muhiddinur Kamal; Zulfani Sesmiarni; Arifmiboy Arifmiboy (KOLONI, 2022)
This research is motivated by the phenomenon from the author's observations about MTs.S Fastabiqul Khairat Gunuang Malintang, Pangkalan Koto Baru District that the Fiqh study teacher has used the Numbered Head Together type of cooperative learning model by first compiling the complete RPP for learning the NHT which the author has uploaded in the appendix section but in reality on the ground that learning using the Numbered Head Together type of cooperative learning model is still rarely carried out by teachers in Fiqh learning in the classroom. This study uses a descriptive qualitative approach. Collecting data in this study the authors obtained through interviews, observation and documentation. The data source of this writing uses the key informant of the Fiqh teacher, and the supporting informant is a class VIII student of MTsS Fastabiqul Khairat Gunuang Malintang. The data analysis technique that the author uses is data reduction, data presentation, and conclusions. Then the data validity technique uses Source Triagulation. . Based on the results of the study, it can be understood that the implementation of the Numbered Head Together (NHT) cooperative learning model in Fiqh subjects uses material and practice. The model used is the Numbered Head Together (NHT) cooperative type in the VIII class fiqh subjects, namely in creating a safe and comfortable learning atmosphere so that the lessons given to students can be well received, namely the teacher can implement the Numbered Head Together (NHT) cooperative model used. ) correctly so that students do not feel bored in learning Keywords: Implementation of the Numbered Head Together Type of Cooperative Learning Model (NHT, Fiqh Subjects)